Analysis of Customer Satisfaction at The Dimalsa Majalengka Store - Kartiwa, Aa; Yani, Yuly; Suzana, Anna; Laras, Salsa Alcindy (Journal of Bussines Management Basic, 2024)
This research aims to analyze customer satisfaction at the Dimalsa Majalengka Store (a case study on Dimalsa Bantarujeg Majalengka). Dimalsa is one of the Micro, Small and Medium Enterprises (MSMEs) which is engaged in a trading business that sells various types of goods, be it Food, Office Stationery (ATK) and Clothing. The sample used in this study amounted to 7 informants. The analytical method used is a qualitative method with data verification using triangulation with the research variable being Quality of Service. The sampling technique was carried out by purposive sampling technique. The results of this study are that the quality of service at the Dimalsa Bantarujeg Majalengka store as a whole is quite good and is in line with expectations. The results of this study indicate that with the existence of physical evidence (tangible) in the form of cleaning equipment and ample parking in accordance with standards, as well as the reliability of its employees who are alert, responsiveness is fast and straightforward, store guarantees make customers believe in shopping at the Dimalsa store and Store empathy for its customers Who provide all the needs of customers